Factors Associated with Unsafe Actions for Kujang Boga Factory Workers, Bubulak Village, West Bogor District, Bogor City in 2023 - Chandra Pratama Hidayat; Wirda Syari; Sugih Setia Raharja (Universitas Ibn Khaldun Bogor, 2023)
Work accidents that occur are influenced by 2 (two) direct causes, namely unsafe action and unsafe conditions. Based on preliminary study data at the Kujang Boga Village Factory, data on unsafe actions such as smoking at work by as many as 25% of 36 workers, not wearing PPE when opening the oven by as much as 25%, and doing work with an unergonomic posture as much as 50% of all these unsafe actions can cause work accidents. This type of research is quantitative research with a cross-sectional approach. The population of this study was 36 Kujang Boga Factory workers with total sampling techniques. The data analysis used is chi-square. The results of the study obtained variables related to unsafe actions, namely knowledge variables (value = 0.001), work attitude variables (p-value = 0.003), PPE availability variables (p-value = 0.000), and K3 supervision variables (p-value = 0.003) while variables that were not related to unsafe actions were motivation (p-value = 0.468). This study concludes that there is a relationship between knowledge, work attitudes, availability of PPE, and K3 sup,ervision with unsafe actions on Kujang Boga Factory workers, Bubulak Village, West Bogor District, Bogor City in 2023. Suggestions for prelude factories to provide PPE with good quality and can be affordable by factory funds and create a reward and punishment system for workers.